The relative contribution of anaerobic and aerobic energy systems during flatwater kayak paddling - Nakagaki, K.; Yoshioka, T.; Nabekura, Y. (Japanese Journal of Physical Fitness and Sports Medicine, 2008)
The purposes of this study were to investigate the characteristics of physiological responses during flat-water kayaking events, and to quantify the contribution of aerobic and anaerobic energy systems. Eight male kayak paddlers participated in the study. The subjects performed an incremental test and five all-out tests (20, 40, 120, 240 and 600 sec) on a kayak ergometer. Peak oxygen uptake (V^^·O_2peak; 3790ml·min^<-1>) in the incremental test was significantly lower than maximal oxygen uptake (V^^·O_2max; 3944ml·min^<-1>) in the all-out test. In contrast, power at V^^·O_2peak (154.0W) was significantly higher than power at V^^·O_2max (144.1W). The contributions of energy systems were calculated by measurements of the accumulated oxygen uptake and accumulated oxygen deficit. The relative anaerobic energy system contributions for 200m (40sec), 500m (120sec), and 1000m (240sec) averaged 71%, 43%, and 26%, respectively. These higher relative anaerobic energy system contributions, due to higher anaerobic capacity in kayak athletes, and the smaller muscle mass involved in kayak paddling limit oxygen uptake when exercise intensity is high. Furthermore, slower exercise cadence in kayak paddling leads to higher muscular tension, and thus may enhance the limiting of oxygen uptake.